1985
DOI: 10.1037/0022-3514.49.3.636
|View full text |Cite
|
Sign up to set email alerts
|

Sex of authority role models and achievement by men and women: Leadership performance and recognition.

Abstract: College students (N = 276) were exposed to all-male, all-female, or mixed-authority role models and then participated in a 4-person mixed-sex discussion. Vicarious cultural experience of authority models was represented by videotaped reenactments of TV commercials. Participants viewed either four traditional commercials showing a man as authority and woman as subordinate, or four reversed-role versions in which the male and female actors switched roles in the same scenarios. Personally observed authority model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…It has been noted that women and men have different perceptions of the world (Estes and Ewert, 1988;Henderson and Bialeschki, 1987) and that women tend to read and interpret others meanings and abilities more accurately than do men (Boice et al 1984;Geis et al 1985;Hall, 1984). Therefore, there were two objectives of this study; first, an attempt was made to determine if gender biases existed in participant perceptions of female and male outdoor leaders.…”
Section: Hypothesesmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been noted that women and men have different perceptions of the world (Estes and Ewert, 1988;Henderson and Bialeschki, 1987) and that women tend to read and interpret others meanings and abilities more accurately than do men (Boice et al 1984;Geis et al 1985;Hall, 1984). Therefore, there were two objectives of this study; first, an attempt was made to determine if gender biases existed in participant perceptions of female and male outdoor leaders.…”
Section: Hypothesesmentioning
confidence: 97%
“…Leaders are perceived as more competent, potent and dominant than followers. In an investigation of leadership recognition and gender roles, Geis et al (1985) found that recognition 'is influenced by the evaluator's expectations, which are at least partly defined by sex of authority role models in the social environment' (p. 636). Estes and Ewert (1988) make similar claims noting that physical skill expectations are lower for females than for males.…”
Section: Introductionmentioning
confidence: 98%
“…There are apparent differences in preferred and expected styles of leadership between females and males (Geis, Boston, & Hoffman, 1985;Winther & Green, 1987). Males tend to prefer and work well under a traditional hierarchical, directive leadership approach where power is in the hands of the "boss" and the rank and file conduct the daily business (Kushell & Newton, 1986).…”
Section: Development Of Gender Identitymentioning
confidence: 97%
“…From the perspective of power relations, gender has been defined by role status (Eaglq, 1987;Geis, Boston, & Hoffman, 1985) and the differential placement of women and men into low and high status role enactments (Crosby, 1987). Similarly to the "gender as difference" perspective, the power domain defines gender relationships as asymmetrical, but clearly privileges one group over the other.…”
Section: Gender As Expression Of Power Relationshipsmentioning
confidence: 99%